The impact of association with the EU on domestic industrial policy making - Campbell, C; Campbell, Carolyn (1999)
﻿ This thesis is a case study of the effects of association with the EU on domestic industrial policy making in Poland during 1990-1995 from a liberal intergovernmentalist perspective, showing how association affected the industrial policy-making autonomy of the Government in relation to other domestic actors in two ways. First, because domestic interests were weak and divided in transition-era Poland, the EU provided political leaders with a sharper focus and allowed them to consolidate domestic support for government industrial policy initiatives. Second, where domestic opposition arose, association helped political leaders to overcome it by giving industrial policy initiatives greater legitimacy and allowing them to be portrayed as "mandatory" for EU membership. The manner in which the Government handled domestic pressure for intervention from state enterprises seeking to avoid painful adjustments and restructuring during the transition offers a prime test of the effects of EU association on industrial policy-making autonomy. In most areas, the pro-market, pro-competition policies mandated by EU association were incompatible with the nature and level of governmental involvement in industry under socialism, requiring an end to state subsidies and other forms of discretionary support enjoyed by state enterprises for nearly four decades. Incorporating case studies of the steel and textiles sectors, this thesis illustrates how in the context of transition, the Government's commitment to EU association was stronger than for other recent EU members and ensured that the Government would deviate from the course charted in the Association Agreement only in cases of intense domestic pressure, and even then only temporarily. Accordingly, in a new twist to liberal intergovernmentalism, Poland's transitional domestic situation coupled with the country's enduring commitment to eventual EU membership ensured that the effects of association on policy-making autonomy were more pronounced in Poland than in existing member states.